PENGARUH MUROTTAL DENGAN KECEMASAN PERSALINAN KALA I PADA IBU PRIMIPARA DI WILAYAH KERJA PUSKESMAS WAY DENTE KABUPATEN TULANG BAWANG - Yulianti, Ria; Sari, Dewi Yulia; Putri, Ratna Dewi; Sari, Nita Evriana (Universitas Malahayati Bandar Lampung, 2022)
Background: Anxiety facing labor is felt by all pregnant women, especially primigravida. In Indonesia, it was found that primigravida mothers experienced severe anxiety reaching 83.4% and moderate anxiety by 16.6% while in multigravida mothers, severe anxiety was 7%, moderate anxiety was 71.5 %, and mild anxiety 21.5%. The purpose: this study is to know the effect of murottal with first stage labor anxiety in primiparous mothers in the working area of the Way Dente Health Center, Tulang Bawang Regency in 2021.Methods: This research was conducted with a quantitative approach. Non-equivalent quasi-experimental analytical research design. The population in this study were all mothers who were about to give birth in the work area of the Way Dente Health Center, Tulang Bawang Regency totaling 44. The sample in this study amounted to 15 respondents in the control group and 15 respondents in the intervention group. The object of this research is: Murotaal therapy for labor anxiety. The time of the research was carried out in March-July 2021. Data collection used an observation sheet. Analysis with univariate and bivariate (T-Test).Results: It is known that the average anxiety before being given murottal is 54.27 and after being given it is 27.00. It is known that the average anxiety before being given care is 51.67 and after being given care is 35.87. Conclusion: There is a Murottal Effect with First Stage Labor Anxiety on Primiparous Mothers in the Working Area of Way Dente Health Center, Tulang Bawang Regency in 2021 p-value 0.000. Suggestions: expected to make promotive efforts for midwifery services so that related institutions can pay more attention to techniques for reducing anxiety during childbirth. Keywords: Murottal, Anxiety, Labor, Primipara ABSTRAK Latar Belakang: Kecemasan mengadapi persalinan dirasakan seluruh ibu hamil khususnya primigravida, Di Indonesia didapatkan bahwa ibu primigravida mengalami kecemasan tingkat berat mencapai 83,4% dan kecemasan sedang sebesar 16,6% sedangkan pada ibu multigravida didapatkan kecemasan tingkat berat 7%, kecemasan tingkat sedang 71,5%, dan cemas ringan 21,5%.Tujuan penelitian: diketahui Pengaruh Murottal Dengan Kecemasan Persalinan Kala I Pada Ibu Primipara Di Wilayah Kerja Puskesmas Way Dente Kabupaten Tulang Bawang Tahun 2021.Metode: Penelitian ini dilakukan dengan pendekatan kuantitatif. Rancangan penelitian analitik quasi eksperimen non equivalen. Populasi dalam penelitian ini adalah seluruh ibu yang akan bersalin di Wilayah kerja Puskesmas Way Dente Kabupaten Tulang Bawang berjumlah 44. Sampel pada penelitian ini berjumlah 15 responden pada kelompok kontrol dan 15 responden pada kelompok intervensi. objek dalam penelitian adalah: terapi murotaal terhadap kecemasan persalinan. Waktu peneltian dilaksanakan pada bulan Maret- Juli 2021.Pengumpulan data menggunakan lembar observasi. Analisa dengan univariat dan bivariat (T-Tes).Hasil: Diketahui rata-rata kecemasan sebelum diberikan murottal adalah 54,27 dan setelah diberikan adalah 27,00. Diketahui rata-rata kecemasan sebelum diberikan asuhan adalah 51,67 dan setelah diberikan asuhan adalah 35,87.Kesimpulan: Ada Pengaruh Murottal Dengan Kecemasan Persalinan Kala I Pada Ibu Primipara di Wilayah Kerja Puskesmas Way Dente Kabupaten Tulang Bawang Tahun 2021 p-value 0,000.Saran: diharapkan melakukan upaya promotif bagi pelayanan kebidanan sehingga institusi terkait bisa lebih memperhatikan teknik penurunan kecemasan pada saat persalinan. Kata Kunci : Murottal, Kecemasan, Persalinan, Primipara